Organic versus mechanistic approaches to system-wide improvement: Reducing delays to critical care. Issue 4 (2nd October 2018) - Bonzo, Sarah M.; Liker, Jeffrey K.; Grams, Keith E.; Dickason, Kimberly S.
Abstract: Increasing pressure towards value-based care has increased focus on patient safety and operational improvement initiatives in healthcare delivery. While improvement efforts have increased since the beginning of the patient safety movement, dissemination of these improvements across the complex health system continues to be a challenge. Senior leaders often want improvements to spread fast and wide throughout the organization. We propose that an organic process of developing localized clarity of objectives and collaborative problem solving between units provides a more effective foundation for extending improvements across the system. We follow a large-scale patient safety effort to reduce the time from admission in the Emergency Department (ED) to arrival in the Intensive Care Unit (ICU) to show how the approach taken by leadership impacts successful extension of improvements across an organization.